Is formal lifelong learning a profitable investment for all of life? : how age, education level, and flexibility of provision affect rates of return to adult education in Colombia - Sohnesen, Thomas Pave (Policy research working paper, 2005)
"Lifelong learning is increasingly being recognized as a primary factor for knowledge diffusion and productivity growth. However, little economic evidence exists on the economic value of lifelong learning for the individual, especially in developing countries. This paper contributes to remedy this shortfall. It investigates one aspect of lifelong learning: returns to formal education across ages. In the absence of long-term longitudinal data, the paper estimates rates of return for simulated re-entry into the education system. The estimations use the method of internal rate of return and are based on observed education-age-earnings profiles from the Colombian national household survey. It finds that rates of return to all levels of education are only slightly smaller for 35 year olds than for young people, thus confirming the profitability of investment in adult education. Tertiary education continues to attract a positive return until late in life, 45-50 years, whereas the economic value of re-entering primary and secondary education is positive up till the age of 40-45. So, formal lifelong learning seems to remain a profitable investment for at least half of life. But lack of part-time work, high tuition fees, and prolonged study time reduce the return. The findings suggest that adult formal education initiatives should focus on the 20 to 40 year olds and be designed flexibly to allow learners to work part time. "--World Bank web site